Efektivitas Penyuluhan Kesehatan dalam Meningkatkan Pengetahuan Remaja Tentang Pencegahan HIV dan AIDS di SMA Al-Hasra - Abul A’la Al-Maududi; Annisa Zahria Putri H; Laisyah Shava Zein H; Naisya Audya Zahra; Lanina Syahdila; Divya Salsabilla; Ariel Ardiansyah (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2026)
HIV and AIDS remain a public health challenge, particularly among adolescents who are vulnerable to risky behaviors. A lack of proper understanding of HIV and AIDS, along with persistent stigma against people living with HIV and AIDS (PLWHA), potentially increases the risk of transmission and hinders prevention efforts. This activity aimed to improve adolescents' knowledge and attitudes regarding HIV and AIDS prevention through health education. The activity was conducted at Al-Hasra High School in Bojongsari District, Depok City, involving 25 students as participants. The method used was interactive education accompanied by pre-test and post-test evaluation. The evaluation results showed an increase in participants' knowledge after the intervention, as reflected in both average scores and the proportion of students in the good knowledge category. These findings demonstrate the critical role of health education in improving adolescents' understanding of HIV and AIDS prevention. Therefore, similar education activities should be conducted continuously as promotive and preventive efforts to reduce the risk of HIV transmission from adolescence.